Changes in the extracellular microenvironment and osteogenic responses of mesenchymal stem/stromal cells induced by in vitro direct electrical stimulation. (February 2021) - Srirussamee, Kasama; Xue, Ruikang; Mobini, Sahba; Cassidy, Nigel J; Cartmell, Sarah H
Electrical stimulation (ES) has potential to be an effective tool for bone injury treatment in clinics. However, the therapeutic mechanism associated with ES is still being discussed. This study aims to investigate the initial mechanism of action by characterising the physical and chemical changes in the extracellular environment during ES and correlate them with the responses of mesenchymal stem/stromal cells (MSCs). Computational modelling was used to estimate the electrical potentials relative to the cathode and the current density across the cell monolayer. We showed expression of phosphorylated ERK1/2, c-FOS, c-JUN, and SPP1 mRNAs, as well as the increased metabolic activities of MSCs at different time points. Moreover, the average of 2.5 μM of H2 O2 and 34 μg/L of dissolved Pt were measured from the electrically stimulated media (ES media), which also corresponded with the increases in SPP1 mRNA expression and cell metabolic activities. The addition of sodium pyruvate to the ES media as an antioxidant did not alter the SPP1 mRNA expression, but eliminated an increase in cell metabolic activities induced by ES media treatment. These findings suggest that H2 O2 was influencing cell metabolic activity, whereas SPP1 mRNA expression was regulated by other faradic by-products. This study reveals how different electrical stimulation regime alters cellular regenerative responses and the roles of faradic by-products, that might be used as a physical tool to guide and control cell behaviour.